Non-cancer human health risk assessment from exposure to cadmium in rice irrigated with water from San Juan River - Fontanilla, Cyreene S.
This study was conducted to determine the Cd concentration in brown and polished rice of different varieties (NSIC Rc 238, 148 and 128) collected from nine farms, within three blocks (Block A, B and C) in Barangay Real, Calamba City irrigated with water from San Juan River. The risk of non-carcinogenic health effects for adults (aged 20 years and older) from long-term consumption of rice with Cd was also evaluated using the non-cancer hazard quotient. Rice grains with hull were collected last November-December 2013 from the nine farms. Brown and polished rice were both analyzed for Cd using Graphite Furnace Atomic Absorption Spectrophotometer (GFAAS). Results showed that brown rice from all nine farms in Barangay Real had a mean Cd concentration of 0.0302 mg/kg, ranging from 0.0062 to 0.0725 mg/kg while polished rice had a mean Cd concentration of 0.0295 mg/kg, ranging from 0.0047 to 0.0778 mg/kg. Thus, Cd concentrations in both brown and polished rice did not exceed the 0.4 mg/kg maximum allowable Cd concentration in rice set by FAO/WHO (2011). Brown (0.0725 mg/kg) and polished rice (0.0778 mg/kg) collected from the farm nearest (about 150m) to the irrigation control gate had the significantly (p = 0.000) highest mean Cd concentrations among the nine farms. The mean Cd concentrations between brown and polished rice did not differ significantly (p.0.05) in all the nine farms, Block A and C, and in the three varieties. This means that residents who prefer to eat brown rice because of its higher nutritional value will not be exposed to significantly higher Cd concentration. In all the nine farms, the NHQ values for adults (aged 20 years and older) were less than 1 in both the brown and polished rice with low Cd contents. Thus, there is no risk of non-carcinogenic health effects for adults from long-term consumption of rice grown in the nine farms in Barangay Real